Gate voltage and drain current stress instabilities in amorphous In–Ga–Zn–O thin-film transistors with an asymmetric graphene electrode - Joonwoo Kim; Sung Myung; Hee-Yeon Noh; Soon Moon Jeong; Jaewook Jeong (AIP Advances, 2015)
The gate voltage and drain current stress instabilities in amorphous In–Ga–Zn–O thin-film transistors (a-IGZO TFTs) having an asymmetric graphene electrode structure are studied. A large positive shift in the threshold voltage, which is well fitted to a stretched-exponential equation, and an increase in the subthreshold slope are observed when drain current stress is applied. This is due to an increase in temperature caused by power dissipation in the graphene/a-IGZO contact region, in addition to the channel region, which is different from the behavior in a-IGZO TFTs with a conventional transparent electrode.